SOCIOECONOMIC DYNAMICS IN THE AGRARIAN SPACE OF CATALAO - GOIAS - Silva, Juniele Martins [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
The Brazilian agrarian space undergoing intense transformations after the second half of the 20th century, especially in 1970s. During this period, there was an expansion of agriculture modernization, which result in a significant increase in agricultural production for export. Goias State and, therefore, the Municipality of Catalao undergoing an intense process of agriculture modernization from 1970. In view of the above, this study aims to understand the agrarian space transformations of Catalao (Goias), focusing the expansion of agriculture modernization from the 1970s. For conducting the study, were performed theoretical and documentary researches. In Catalao (Goias), in the same way as in Brazil, the agriculture modernization did not occur homogeneously, favoring land concentration, reaching areas of chapada (flat terrain) and benefiting the medium and large landowners / rural producers.
Keywords: Agriculture modernization; Goias State; Municipality of Catalao (Goias)